THE TEA TIME HAS CHANGED IN AZORES - Mário Moura (European Scientific Journal, ESJ, 2014)
This article focuses in the azorean third tea period (1878-1879), time to learn and the first move towards tea industry. This time is made up of two periods: First, time to collect and make tea (March to July 1878); Second, time to collect and make tea (April to July 1879). With the hiring of two Chinese tea technicians, Lau-a-Pan (the master) and Lau-a- Teng (the interpreter) by the local agricultural society, locals rapidly acquired two things: how to grow and make tea and the value of his tea. Tea industry brought together first and second generation SPAM members, who, to cope with wine and orange crises, among other products, invested in tea. Industry mainly developed in Saint Michaels‘s Island.